MythomaniaS: Crime Scenes & Psycho Case Studies - Roche, François; Lacadée, Camille (Punctum Books, 2015)
mythomaniaS is a catalog of case studies in the form of film stills, architectural fragments, stage props, texts, and images culled from the experiments of MindMachineMakingMyths (Lab M4, part of the New Territories architecture studio, Bankgok, Thailand), a collaboration begun in 2012 between Camille Lacadee and François Roche to construct environmental-architectural psycho-scapes (in the partly fabricated wilds of various countries) as laboratory-shelters for exploring and deconstructing the supposed rifts between realism and speculative fiction (myth), psyche and environment, body and mind. Bringing together architecture, Deleuze and Guatarri's schizoanalysis and deterritorialization, and Alfred Jarry's pataphysics (the "science of imaginary solutions which symbolically attributes the properties of objects, described by their virtuality, to their lineaments"), Lacadee and Roche (and their tribe, Ezio Blasetti, Stephan Henrich, Danielle Willems, Gwyll Jahn, and many others) enacted and filmed mise-en-abymes in which certain scripted para-psychic narratives and architectural structures merge in the pursuit of reclaiming resilience - described by Roche as a tactic for merging refusal and vitality into a schizophrenic logic able to navigate the antagonism between the bottom-up and top-down conditions of the globalized world. In these fabricated schizoid psycho-nature-machine-scapes, the human being is no longer a bio-ecological consumer but a psycho-computing animal that emerges co-dependently with its environment in a hyper-local haecceity ("this-ness").